If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 7 + c = -14 + 13c + 21 Reorder the terms: 7 + 2c + c = -14 + 13c + 21 Combine like terms: 2c + c = 3c 7 + 3c = -14 + 13c + 21 Reorder the terms: 7 + 3c = -14 + 21 + 13c Combine like terms: -14 + 21 = 7 7 + 3c = 7 + 13c Add '-7' to each side of the equation. 7 + -7 + 3c = 7 + -7 + 13c Combine like terms: 7 + -7 = 0 0 + 3c = 7 + -7 + 13c 3c = 7 + -7 + 13c Combine like terms: 7 + -7 = 0 3c = 0 + 13c 3c = 13c Solving 3c = 13c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-13c' to each side of the equation. 3c + -13c = 13c + -13c Combine like terms: 3c + -13c = -10c -10c = 13c + -13c Combine like terms: 13c + -13c = 0 -10c = 0 Divide each side by '-10'. c = 0.0 Simplifying c = 0.0
| -35=-8(-4x-7)-7(3+6x) | | 7n+3/2n=30 | | x^2+1=6x-4 | | -7/12-7/12 | | 13x-7y=5 | | 33=-3(6b+3)-8(2+5b) | | 3/8*3 | | mx-5x=y | | 2x^3-12x^2+28x=0 | | 72=6(6x-8)+6(7x+7) | | 4x-12=2x-2 | | 5g-8=12(1/4g-1/3)+10 | | -2(-4x-1)=26 | | 2x^2+7=x^2+12 | | 4x^2-11x+25=6x+7 | | (3/8)/3=N/1 | | -52=-4(-4x-6)+4(1-8x) | | 8x+8=10x+10 | | 2/60 | | 3/5(k+1)=1/4(2k+4) | | 6-4x=-2x-2 | | (50+4)(9-7)=118 | | 2(x+4)=(x+7) | | 0=2(x-7) | | 0.5+0.3=0.7-0.3 | | -5x+6x=-8 | | 18m=f | | 12x(x-35)x(x-46)=360 | | 5x+7=-4+3x+23 | | w-3a=m | | 21=x-7-8x | | -7=9-50+x |